OVERVIEW OF PERIPHERAL NEUROPATHY IN CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS AT DR. MOHAMMAD HOESIN HOSPITAL PALEMBANG - Christin, Theresia; Ali, Zulkhair; Legiran, Legiran; Ferawaty, Ferawaty (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2023)
Neurological complications occur in almost 60% of patients with advanced CKD and affect the nervous system at all levels, both central and peripheral. Peripheral neuropathy in CKD is usually asymptomatic until renal function is below 15%, and glomerular filtration is less than 10-12 ml/min. This study seeks to identify and characterize peripheral neuropathy in patients with chronic kidney disease undergoing hemodialysis at Dr. Mohammad Hoesin Hospital Palembang. This is a descriptive cross-sectional study with the research sample comprising chronic kidney disease patients undergoing hemodialysis at Dr. Mohommad Hoesin Palembang Hospital. The distribution of research subjects based on the Neuropathy Symptom Score (NSS) revealed that 65.7% fell into the mild neuropathy category, based on an NSS of 3-4. According to the electrophysiology results, 82.9% of patients exhibited peripheral neuropathy, while 17.1% showed normal NCS results. Sensory motor neuropathy accounted for 51.4%, including 71.5% with axonal neuropathy, 11.4% with axonal-demyelinating lesions, and no demyelinating lesions. The high prevalence of peripheral neuropathy in CKD patients identified through electrophysiological examination (ENMG) emphasizes the importance of nerve conduction examination as a diagnostic tool for peripheral neuropathy in CKD patients. This can aid in determining the progression of peripheral neuropathy in CKD patients, allowing for appropriate management and prevention of disability complications to enhance the quality of life for these individuals.